Feasibility Study Estimation Of Water Usage In USM Engineering Campus Hostels - Suhaimi, Nik Siti Ayeesha Nik (Universiti Sains Malaysia, 2022)
This research project aimed to calculate the water usage in USM Engineering Campus hostels using two approaches, first one using approximation based on water meter in one of the hostel building in the campus and another approach is using information from questionnaire. Then, the differences between those two methods were observed and discussed. There are three objectives needed to be followed, with first one is to find the difference is water usage between female and male students, second one is the effect of weather to human behavioural trends in using water and lastly is the determination of percentage of estimation error between the two approaches of calculating water usage at the site of the study, which is the USM Engineering Campus. In first method, to calculate the water usage, a questionnaire was made to estimate the water usage per person in each hostel. Certain internal factors, such as gender, age and ethnicity were included in the questionnaire to see the significance of them to the water usage. The questions will ask students on how much time they take a bath, for toilet, brushing teeth and even cooking, for three different weather condition. The information later will be used to calculate water usage of a student in each hostel in three different weather condition, subjected to temperature. By average, a female student used 0.246 m3 water daily while a male student used 0.236 m3 of water daily. Then, in context of weather condition, by average, a student used up to 0.421 m3 in hot weather, meanwhile in average, the water usage per person is 0.241 m3. During cold weather, a student use 0.209 m3 of water daily. Second method is where water usage is calculated using approximation based on SH1’s water usage. Then, the percentage of estimation error was calculated for each hostel where SH4 having the highest percentage with 32.62% and SH5 having the lowest percentage with 20.89%. In term of water conservation, data shown students living in hostels saved more water than students at home.